SWOT Analysis and Preliminary Study on Prevention and Control Management of Temporary Integrated Isolation Ward During COVID-19 Outbreak - Zhou, Ye; Bai, Lixiang; Guo, Hao; Guo, Shaowei; Han, Xiaowen; Yue, Ning J.; Li, Qingxia (Frontiers in Public Health, 2021)
Background: The world faced crises of prevention and control and shortage of medical resources during COVID-19 (Corona Virus Disease 2019) Outbreak. The establishment of temporary integrated isolation wards in hospitals, which is universal and representative in China, is one of the most effective strategies to solve these problems according to China's experiences. Aim: To conduct a preliminary study on the establishment of temporary integrated isolation ward during the outbreak of COVID-19 and to evaluate the related impacts. Methods: SWOT analysis was used to analyze the advantages, disadvantages, opportunities and risks in the establishment of temporary integrated isolation ward, and corresponding corrective measures were made according to the analysis results. Findings: The ward has formulated more than 10 related work procedures and prevention and control measures. A total of 93 patients with 18 critically ill patients were admitted for treatment and isolation. They were all evaluated based on the established procedures and protocols. 24 supplementary nucleic acid tests were ordered and conducted. 1 new patient with COVID-19 was confirmed and was successfully transferred to the designated COVID-19 infectious control hospital. There were no missed diagnosis or misdiagnosis, no cross-infection of patients, no cluster outbreak, no infection of medical workers in the entire process. Conclusion: SWOT analysis is helpful to guide the establishment of temporary integrated isolation ward and the formulation of prevention and control measures in Hebei General Hospital during COVID-19 outbreak. It provides the guidance and reference of significance for the establishment of similar type of wards in the future.